ANALISIS IMPLEMENTASI KURIKULUM TEKNIK SEPEDA MOTOR-HONDA DI SMK PANCASILA SURAKARTA - Wiwit Riyanti; Suharno Suharno; Danar Susilo Wijayanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
This research aims to know: (1) relevance of learning school with Honda; (2) implementation of curriculum techniques motorcycles Honda in Vocational High School Pancasila Surakarta; (3) evaluation curriculum techniques motorcycles Honda in Vocational High School Pancasila Surakarta. This research is evaluative research. Data source derived from 98 students TSM-Honda, headmaster, Deputy Headschool of curriculum, curriculum development division Honda. Data techniques include by questionnaire, interview, observation, and documentation. This research used logic validity or reasoning that instrument is valid based on rational analysis. Apparatus are arranged based on reasoning should be referred to experts so this instrument truly intelligent before distributed to respondents. The procedure consists research method, determine, devise research instruments, data retrieval, data analysis, the withdrawal of conclusion. The conclusion is: (1) curriculum implementation of Motorcycle-Honda Engineering is composed of four aspects context, planning, execution and evaluation, curriculum implementation of Honda overall reaches 72% with a high category; (2) context aspect reaches 78% with top grade. This means that the aspect context which includes the relevance of learning school with Honda and Honda-TSM program eligibility is already proper; (3) planning aspect reached 68% with a high category. Aspects planning that includes an input of students, the quality of the applicants, the parties involved, the training of teacher preparedness, Honda's been good; (4) implementation aspect of the reach 74% with a high category. Implementation aspects of administrative arrangement that includes teaching, learning materials, tools and materials, media of learning, learning methods are already good; (5) evaluation aspect reached 67% with a high category. An evaluation includes elements of competency teachers, students, students ' value competency, communication with Honda, the success of curriculum, curriculum development is already good.